2005
DOI: 10.1038/sj.npp.1300833
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Ethanol Intoxication Induces Behavioral Sensitization in the Absence of a Sensitized Accumbens Dopamine Response in C57BL/6J and DBA/2J Mice

Abstract: Repeated exposure to drugs of abuse results in an increased sensitivity to their behavioral effects, a phenomena referred to as behavioral sensitization. It has been suggested that the same neuroadaptations underlying behavioral sensitization contribute to the maintenance and reinstatement of addiction. Dysregulation of dopamine (DA) neurotransmission in the mesoaccumbens system is one neuroadaptation that is thought to lead to the compulsive drug-seeking that characterizes addiction. Evidence that sensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 56 publications
3
91
1
Order By: Relevance
“…For instance, ethanol increases extracellular dopamine levels in the NAc of mice sensitive to the locomotor stimulant effects of ethanol, including FAST mice (Meyer and Phillips, 2004), DBA/2J mice (Zapata et al, 2006) and outbred NMRI mice (Larsson et al, 2002). In addition, administration of a dopamine D2 receptor antagonist, or combined D1-D2 receptor antagonism, attenuates the locomotor stimulant response to ethanol in FAST mice (Shen et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ethanol increases extracellular dopamine levels in the NAc of mice sensitive to the locomotor stimulant effects of ethanol, including FAST mice (Meyer and Phillips, 2004), DBA/2J mice (Zapata et al, 2006) and outbred NMRI mice (Larsson et al, 2002). In addition, administration of a dopamine D2 receptor antagonist, or combined D1-D2 receptor antagonism, attenuates the locomotor stimulant response to ethanol in FAST mice (Shen et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthering this role, NAC Homer2b overexpression in B6 mice is sufficient to enhance the dopamine and glutamate response to acute alcohol and to augment alcohol-induced neurochemical sensitization ( Figure 5). Thus, as observed for behavior, NAC Homer2b overexpression 'presensitizes' the capacity of alcohol to elevate NAC levels of dopamine and glutamate in B6 miceFa neurochemical phenotype akin to that produced by repeated alcohol experience (eg Doyon et al, 2005;Melendez et al, 2002;Middaugh et al, 2003;Szumlinski et al, 2006aSzumlinski et al, , 2007Weiss et al, 1993; but see Zapata et al, 2006). Whether the alcohol 'presensitized' neurochemical phenotype produced by NAC Homer2b overexpression relates to an upregulation in mGluR-Homer2-NMDA signaling cannot be discerned from the present study.…”
Section: Accumbens Homer2b Upregulation Promotes Alcohol Rewardmentioning
confidence: 99%
“…Although the VTA is critical for the development of sensitization for many abused drugs, the direct role of the VTA in expression of sensitization may depend on the particular drug of abuse, where a clearer role for opiates but a less clear role for psychostimulants has been described ( Leite-Morris et al 2004;Vanderschuren and Kalivas 2000). In addition, a recent study showed that ethanol-related sensitization in mice can be apparent without increased dopamine release, perhaps dissociating the dopaminergic system from enhanced locomotor activation by ethanol after repeated ethanol exposure in mice (Zapata et al 2006). Although little is known about the cellular mechanisms underlying enhanced locomotor activation after repeated ethanol exposure, reduced SK and facilitation of NMDA-induced bursting might contribute to the enhanced locomotor activation by cocaine after repeated ethanol exposure that we and others (Itzhak and Martin 1999) have observed.…”
Section: Repeated Ethanol Treatment Enhanced Locomotor Activation By mentioning
confidence: 99%